THOUGHTS OF OUR GRANDFATHER IBN SINA IN THE DEVELOPMENT OF CHILDREN’S PHYSICAL ABILITIES: THOUGHTS OF OUR GRANDFATHER IBN SINA IN THE DEVELOPMENT OF CHILDREN’S PHYSICAL ABILITIES - ataqulov, murotqosim (Физическое воспитание, спорт и здоровье, 2022)
This article provides information on the role and importance of sports in the development of physical and mental abilities of schoolchildren